Extraction and characterization of gelatin from different marine fish species in Malaysia - Jaswir, Irwandi; S., Faridayanti; Mirghani, Mohamed Elwathig Saeed; Mohd Salleh, Hamzah; Hassan, Torla; Che Man, Yaakob (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Gelatins from the skin of four local marine fish, namely “kerapu” (Epinephelus sexfasciatus), “jenahak” (Lutjianus argentimaculatus), “kembung” (Rastrelliger kanagurta), and “kerisi” (Pristipomodes typus) have been successfully extracted by acid extraction. Results characterization showed that the fish gelatins were comparable to the fish gelatins from other fish species previously reported. They appeared snowy white in color with crystal-like and light texture. The gelatine extracted from “kerapu” had the strongest fishy odor, followed by the gelatines derived from “jenahak”, “kembung” and “kerisi”. In terms of bloom strength, the gelatin extracted from “kerapu” was found to be the strongest one compared to others, with the bloom value of more than 2000 g. The gelatins developed in this study contained almost all essential amino acids, with glycine being the most predominant one.